2020
DOI: 10.3390/ma13071783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Primary Stability of Porous Tantalum and Titanium Acetabular Revision Constructs

Abstract: Adequate primary stability of the acetabular revision construct is necessary for long-term implant survival. The difference in primary stability between tantalum and titanium components is unclear. Six composite hemipelvises with an acetabular defect were implanted with a tantalum augment and cup, using cement fixation between cup and augment. Relative motion was measured at cup/bone, cup/augment and bone/augment interfaces at three load levels; the results were compared to the relative motion measured at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Advances in the material coating of shells and augments have given surgeons great confidence in using these implants due to their improved bone purchase and faster osseous integration. 13 Cadaveric studies have demonstrated significant improved when combining porous coated shells (Gription) with trabecular metal augments compared to traditional uncemented shells (Porocoat) and trabecular metal augments. 14 However, they are not without their disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the material coating of shells and augments have given surgeons great confidence in using these implants due to their improved bone purchase and faster osseous integration. 13 Cadaveric studies have demonstrated significant improved when combining porous coated shells (Gription) with trabecular metal augments compared to traditional uncemented shells (Porocoat) and trabecular metal augments. 14 However, they are not without their disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…For THA revision, modular and revision multi-hole porous Ta shells are available ( Figure 10 ). Owing to their low elastic modulus, high friction coefficient, and superior osteoconductivity, porous Ta shells are beneficial for maintaining or even increasing the bone mass of the adjacent acetabulum and contribute to revision surgery, when needed ( Vutescu et al, 2017 ; Beckmann et al, 2020 ). In a prospective study ( Macheras et al, 2008 ) with 8–10 years of follow-up of 151 hips after primary THA, although the periacetabular gaps of length 1–5 mm were found in the early 25 acetabular cups, the aforementioned gaps disappeared after 24 weeks.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For this purpose, markers are attached to the implant as well as to the bone to measure the micromotions between the components under loading conditions. The translational motions between the implant and the bone are often below 100 μm and rotations far below one degree can occur [ 12 14 ]. Due to improvements of marker-based measurement systems in the last decades, these systems were also used for these biomechanical research areas, where high accuracies are needed.…”
Section: Introductionmentioning
confidence: 99%